The Association between Carbohydrate Intake and Periodontal Health in the Elderly - FS Emadi Majd; R Ghadimi; SR Hosseini; A Bijani; N Jenabian; M Motalebnejad; E Mahmoudi; ZS Madani; MM Naghibi; F Baladi; F Sayadi; M Mehryari; et al. (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul, 2022)
Background and Objective: Periodontal disease is one of the most common chronic oral diseases worldwide. A variety of foods may affect periodontal health. Due to the importance of periodontal health in the old age, this study was designed to investigate the association between carbohydrate intake and periodontal health in the elderly in Amirkola, northern Iran. Methods: This cross-sectional study is part of the second phase of the Amirkola Health and Ageing Project (AHAP). The evaluated participants included 400 elderly people (200 men and 200 women). Socio-demographic data of all subjects were recorded in the information form. Periodontal status, including plaque index (PI), periodontal disease index (PDI) and Oral Hygiene Index (OHI) were evaluated. Then, the Semi-Quantitative Food Frequency Questionnaire (SQFFQ) was completed in order to receive daily carbohydrates in grams per day for all Participants. Then, the relationship between carbohydrate intake and periodontal health was evaluated. Findings: The participants consumed an average of 316±102.4 gr/day carbohydrates. The mean range of PI, OHI, PDI and in the high carbohydrate intake (>300 gr) group were 2.18±1.39, 2.84±1.51 and 1.51±0.86, respectively, and this rate was lower than the group with low carbohydrate intake (<300 gr) (1.96±1.52, 2.56±1.53 and 1.37±0.91), but the difference between the two groups was not significant. Conclusion: In the present study, there was no relationship between periodontal health indices and carbohydrate intake.